P024 Real-world experience of Tocilizumab withdrawal in GCA. (23rd April 2022) - Khalid, Salema; Davidson, Brian; Hopkinson, Neil; Mason, Alice; Malik, Mariam; Laskou, Faidra; Parker, Lucy
Abstract: Background/Aims: Part 2 of the GIACTA trial explored the maintenance of efficacy in giant cell arteritis (GCA) patients. It showed that nearly half the patients treated with weekly tocilizumab (TCZ) maintained remission, though flares did still occur in the remaining half when TCZ was discontinued. Currently, NHS England has approved the use of TCZ in GCA for only 1 year as this duration was agreed upon by clinical experts to be sufficient to sustain remission. However, this remains a point of concern amongst clinicians as to whether data from real-life patients confirms that 1 year of TCZ can achieve sustainable remission. Methods: Our objective is to assess the real-world experience of TCZ withdrawal in GCA patients and how different centres are trying to mitigate risk of relapse after its cessation. We are conducting a patient survey across six hospitals in Wessex, United Kingdom. Our aim is to assess the change in clinical features, acute phase reactants and the rate of sustained remission and relapse. Results: 53 patients with GCA were included in the survey. Average age of patients was 73.5 years. 36 patients had cranial GCA, five had large vessel vasculitis and no sub-type was mentioned for the 12 remaining patients. Temporal artery biopsy was the most common diagnostic tool used for 21 patients, followed by PET scan for 14 patients. Eight patients had a clinical diagnosis only, while seven were diagnosed with GCA based on findings of Anterior Ischaemic Optic Neuropathy. Only three patients had their diagnosis confirmed via ultrasound temporal arteries. Out of these 53 patients, 45 started Tocilizumab. 15 patients stopped treatment due to side effects. Of the remaining 30 patients, only 17 have completed their 1 year of TCZ so far. Two patients relapsed 6 months after stopping TCZ. One of them was on methotrexate (MTX) and low dose prednisolone, while other was on mycophenolate mofetil only. Of those who are currently stable since completing TCZ, five patients are on MTX with prednisolone, one patient on leflunomide and prednisolone, four patients on prednisolone only and three patients on MTX only. Two patients are on no treatment currently. Conclusion: This is an ongoing study. Our figures so far show that most patients are still on treatment with steroids and MTX, either alone or in combination, after completing 1 year of TCZ. This could be due to clinicians trying to mitigate against relapse once TCZ is withdrawn. This study highlights that real-world data on relapse/remission rates following TCZ withdrawal is essential as it will help shape future GCA treatment and guidelines. Disclosure: S. Khalid: None. B. Davidson: None. N. Hopkinson: None. A. Mason: None. M. Malik: None. F. Laskou: None. L. Parker: None.